Individual differences in cooperative communicative skills are more similar between dogs and humans than chimpanzees. (April 2017) - MacLean, Evan L.; Herrmann, Esther; Suchindran, Sunil; Hare, Brian
Abstract : By 2.5 years of age humans are more skilful than other apes on a set of social, but not nonsocial, cognitive tasks. Individual differences in human infants, but not chimpanzees, Pan troglodytes, are also explained by correlated variance in these cooperative communicative skills. Relative to nonhuman apes, domestic dogs, Canis familiaris, perform more like human infants in cooperative communicative tasks, but it is unknown whether dog and human cognition share a similar underlying structure. We tested 552 dogs in a large-scale test battery modelled after similar work with humans and nonhuman apes. Unlike chimpanzees, but similarly to humans, individual differences in dogs were explained by correlated variance in skills for solving cooperative communicative problems. Direct comparisons of data from all three species revealed similar patterns of individual differences in cooperative communication between human infants ( N   =  105) and domestic dogs ( N   =  430), which were not observed in chimpanzees ( N   =  106). Future research will be needed to examine whether the observed similarities are a result of similar psychological mechanisms and evolutionary processes in the dog and human lineages. Highlights: We assessed individual differences in cognition in dogs, chimpanzees and human infants. Dogs and humans exhibited similar patterns of correlation in social cognitive skills. The patterns common to dogs and humans were not observed in chimpanzees. Results were similar for three different dog populations with diverse histories. The structure of dog social cognition may be convergent with that of humans.